2012
DOI: 10.1088/0022-3727/45/38/382001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of weak plasma series resonance heating in the H-mode of neon and neon/argon inductively coupled plasmas

Abstract: Phase-resolved optical emission spectroscopy measurements in argon and neon inductively coupled plasmas (ICPs) have revealed a surplus of high-energy electrons in neon-containing plasmas. Differences between results of emission model analyses using neon and argon lines (as well as probe measurements) also indicate a high-energy enhancement in neon-containing plasmas. The abundance of these extra high-energy electrons is correlated with the sheath thickness near the rf antenna and can be reduced by either addin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 16 publications
5
46
0
Order By: Relevance
“…They also carried out optical absorption spectroscopy (OAS) measurements and reported the 1s i levels populations. [17] They also obtained the populations of the 2p 5 3s fine-structure levels by OES branching fraction method and their values agreed with the values obtained from OAS measurements. However, they mentioned that the OAS results are more accurate and within the error bar of 15%.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…They also carried out optical absorption spectroscopy (OAS) measurements and reported the 1s i levels populations. [17] They also obtained the populations of the 2p 5 3s fine-structure levels by OES branching fraction method and their values agreed with the values obtained from OAS measurements. However, they mentioned that the OAS results are more accurate and within the error bar of 15%.…”
Section: Introductionsupporting
confidence: 72%
“…Further, to demonstrate the applicability, the present CR model is applied to the diagnostics of low-pressure Ne-Ar mixture plasma by Boffard et al [17] They reported the spectroscopic measurements of Ne-Ar mixture plasma for a radio frequency discharge at 600 W power. The plasma column was cylindrical with 50 cm diameter and 15 cm height.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Klick et al demonstrated that the detection of the PSR oscillations by a current sensor implemented into the grounded chamber wall allows determining the electron density and temperature via Self-Excited Electron Resonance Spectroscopy (SEERS) [35,53]. Self-excited oscillations are not limited to CCRF plasmas, but can be found in various other types of bounded plasmas, such as inductively coupled plasmas operated in the E-mode [54,55] or hybrid combinations of inductively/capacitively coupled plasmas [56,57], too.…”
Section: Introductionmentioning
confidence: 99%